Decomposition of biowaste macronutrients, microbes, and chemicals in black soldier fly larval treatment: A review. (December 2018) - Gold, Moritz; Tomberlin, Jeffery K.; Diener, Stefan; Zurbrügg, Christian; Mathys, Alexander
Highlights: Black soldier fly larvae biowaste processing is an emerging treatment technology. It produces products that can positively impact the economics of waste treatment. Much can be learned on process mechanisms from well-studied fly species. Protein and carbohydrate quantity and quality are important drivers of process performance. Microbes contribute to process performance. Abstract: Processing of biowaste with larvae of the black soldier fly, Hermetia illucens L. (Diptera: Stratiomyidae), is an emerging waste treatment technology. Larvae grown on biowaste can be a relevant raw material for animal feed production and can therefore provide revenues for financially viable waste management systems. In addition, when produced on biowaste, insect-based feeds can be more sustainable than conventional feeds. Among others, the scalability of the technology will depend on the availability of large amounts of biowaste with a high process performance (e.g. bioconversion of organic matter to proteins and lipids) and microbial and chemical product safety. Currently, in contrast to other waste treatment technologies, such as composting or anaerobic digestion, the process performance is variable and the processes driving the decomposition of biowaste macronutrients, inactivation of microbes and fate of chemicals is poorly understood. This review presents the first summary of the most important processes involved in black soldier fly larvae (BSFL) treatment, based on the available knowledge concerning five well-studied fly species. This is a starting point to increase understanding regarding the processes of this technology, with the potential to increase its efficiency and uptake, and support the development of appropriate regulations. Based on this review, formulating different types of biowaste, e.g. to produce a diet with a similar protein content, a balanced amino acid profile and/or pre- and co-treatment of biowaste with beneficial microbes, has the potential to increase process performance. Following harvest, larvae require heat or other treatments for microbial inactivation and safety.